2016
DOI: 10.15342/ijms.v3i1.86
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Disease Activity and Hearing Loss in Rheumatoid Arthritis Patients A Case Control Study

Abstract: Objectives: Rheumatoid arthritis (RA) is well known to affect many different organ systems. Previous work suggests that this includes the auditory system. The objectives of this work are to evaluate the pattern of hearing impairment in patients with rheumatoid arthritis and to examine the possible associations between hearing impairment and related RA features especially disease activity. Materials and methods: Thirty RA patients (mean age of 44.5 ± 9.9 years; female sex (90%)) and 17 healthy controls (mean ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The study showed that RA patients had nearly doubled probability of developing a hearing impairment than those without RA. Furthermore, they confirmed that hearing loss risk is related to RA rising with age [11], while Rkain et al [16] found that HL was more prevalent in patients with RA compared to healthy groups. Among RA patients 43.4% had conductive hearing loss, 3.3% sensorineural, and 10% mixed hearing loss.…”
Section: Introductionmentioning
confidence: 83%
“…The study showed that RA patients had nearly doubled probability of developing a hearing impairment than those without RA. Furthermore, they confirmed that hearing loss risk is related to RA rising with age [11], while Rkain et al [16] found that HL was more prevalent in patients with RA compared to healthy groups. Among RA patients 43.4% had conductive hearing loss, 3.3% sensorineural, and 10% mixed hearing loss.…”
Section: Introductionmentioning
confidence: 83%
“…Ototoxic drugs which were taken by the child may have caused inner ear damage that lead to sensory neural component of hearing loss. The presence of a mixed type of hearing loss suggested a multifocal involvement of the audiological system in RA [5].…”
Section: /4mentioning
confidence: 96%
“…Conductive hearing loss in RA may be related either to stiffness or to discontinuity of the ossicles in the middle ear [5]. Since the child was under immunosuppressants, she is vulnerable for infections leading to recurrent ear infection.…”
Section: /4mentioning
confidence: 99%
See 2 more Smart Citations